PENGARUH SISTEM REKLAMASI AIR LIMBAH TERHADAP KONSENTRASI BOD DAN COD EFFLUENT INSTALASI PENGOLAHAN AIR LIMBAH SUWUNG DENPASAR - Putra Prabawa, I D. G.; Dharma Putra, K. G.; Suaniti, Ni Made (Jurnal Kimia (Journal of Chemistry), 2013)
The application of water reclamation system has been researched for the concentration of Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) in the effluent waste water treatment in Suwung Denpasar. The aims of the research were to determine the effect of each stage of water reclamation system on the BOD 5 and COD of the effluent, the effectiveness of the water reclamation system and the quality of the reclaimed water. The results showed that each stage of water reclamation system can decrease the concentrations of BOD 5 and COD from waste water treated with different percentage of  reduction. The percentages of the COD reduction by first stage (biological filtration systems) were 41.17% and 31.23% respectively BOD 5 and COD. The second stage (pre-ozonation system) were 83.13% and 77.68% respectively. Moreover, the third stage (coagulation and membrane systems) reduced 29.25% and 8.02% respectively. The overall rate of effectivenes from the initial to final stages of waste water reclamation were 92,98% for BOD 5 and 85,88% for COD.
Keywords: reclamation system, effectiveness, effluent, reclaimed water.